2008
DOI: 10.1080/13693780701488373
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping ofParacoccidioides brasiliensisdirectly from paraffin embedded tissue

Abstract: Based on polymorphisms of the gp43 precursor gene, genotyping of Paracoccidioides brasiliensis was achieved in 6 out of 10 paraffin-embedded tissue samples by modifying a nested PCR procedure used in the diagnosis of the fungal infection. Nine of the samples originated in Brazil. Three sequences were identical to a previously published consensus sequence identifying the P. brasiliensis isolates as members of the formerly named species 1. In contrast, two sequences revealed substitutions identical to isolates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…americana and P . brasiliensis samples from Southeast Brazil (Rio de Janeiro, São Paulo and Minas Gerais) were retrieved for counts [12, 14, 3642]. These three states are located in the Southeastern part of Brazil, a hot spot of PCM, and contain the majority of currently genotyped strains of Paracoccidioides .…”
Section: Methodsmentioning
confidence: 99%
“…americana and P . brasiliensis samples from Southeast Brazil (Rio de Janeiro, São Paulo and Minas Gerais) were retrieved for counts [12, 14, 3642]. These three states are located in the Southeastern part of Brazil, a hot spot of PCM, and contain the majority of currently genotyped strains of Paracoccidioides .…”
Section: Methodsmentioning
confidence: 99%
“…Since gp43 is a highly polymorphic gene that clearly separates the four cryptic species of P. brasiliensis (Matute et al 2006a, Carrero et al 2008, Teixeira 2008, PCR based on this genomic region is now indicated not only for pathogen detection, but also for genotyping of clinical samples. By using this strategy, Ricci et al (2008) evaluated and distinguished between S1-PS2 from paraffin-embedded tissue.…”
Section: Pathogen Detection -Clinical and Environmental Sourcesmentioning
confidence: 99%
“…Molecular identification was conducted by sequencing the gp43 gene of P. brasiliensis extracted from paraffin-embedded tissue using the para I and para IV primers, as described in the literature. 10 Disseminated disease was confirmed with multiple cutaneous abscesses, lung injury, and significant impairment of adrenal, reticuloendothelial, osteoarticular, and integumentary systems, which were noted on thoracic and abdominal computed tomography ( Figure 2). The patient tested negative for HIV-1 and -2 and hepatitis B and C. Amphotericin B complex lipid induction therapy was initiated at 200 mg/day for 20 days, followed by maintenance treatment with TMP-SMX 800/160 mg, twice daily.…”
Section: Casementioning
confidence: 98%